Commoning the State Forest: Crafting Commons through an Indonesian Social Forestry Program - Haudec Herrawan; Nurhady Sirimorok; Munajat Nursaputra; Emban Ibnurusyd Mas'ud; Fatwa Faturachmat; Andi Sadapotto; Supratman Supratman; Yusran Yusran; Muhammad Alif K. Sahide (Forestry Faculty, Universitas Hasanuddin, 2022)
Studies of the commons grew out of responses to Hardin's bleak prediction of “tragedy of the commons,” that without state intervention or privatization, any commons will eventually be destroyed by allegedly self-interested users. As such, the commons studies traditionally tend to demonstrate cases where common pool resources (CPR) can be sustainably managed by groups of people beyond the state and market interventions. This paper shows a case from Sulawesi, Indonesia, where a state social forestry program can create a space for the program beneficiaries to build a commons. Through fieldwork that involves participant observation and in-depth interviews with program extension workers and beneficiaries in two social forestry farmer groups, this study found that the program can stimulate beneficiary groups to build collective action in managing the state forest plots admitted to them and that the two groups are the only successful ones among 14 neighboring groups that are involved in the same program. The study also shows that the management of the state-sponsored commons requires extension workers with deep knowledge about local people and landscape, economic incentives, and the flexibility of the local state agency in bending the rules based on bottom-up demands. Therefore, the case study shows that, on the one hand, the state program can actually stimulate the creation of the commons. On the other hand, commoning seems to be the only way to ensure a successful social forestry program.